Decision System Analysis of Advertising Agency Decisions - Na, W.; Marshall, R.; Woodside, Arch (Emerald Group, 2009)
Purpose – The purpose of this paper is to report the use of decision system analysis (DSA) mapping the streams of communications (i.e. interactions), thoughts, actions and decisions involved for advertising agencies as executives in these firms gain client approval, and design creative, promotional and media strategies. Design/methodology/approach – This study uses DSA. This little-used technique requires protocol analysis, interviews and observation before transcription of the organizational decision processes into flow charts. Findings – The research first identifies four models, describing four specific decision types, then derives a general model from them. Executives from four agencies not in the original sample later confirms the models. The models generally confirm the existing knowledge base, with a few minor exceptions. Research limitations/implications – This qualitative technique suffers the common malady of the researchers losing objectivity because of their immersion in the case-companies. Wherever possible the research employs quantitative techniques to verify observational judgments. Practical implications – The “thick description” and the summary charts of the advertising agency decision processes have the potential to aid agency decision makers to better structure their decision processes. Originality/value – The findings themselves are of significance to those involved in the advertising industry, and there is an element of originality in the classification and the thick descriptions of advertising agency decision systems. The resurrection of DSA and the demonstration that the technique is viable and valuable is also a contribution of the study.